Section News. Issue 3 (March 2016) - Unknown
Abstract: Section Columns from: Evolutionary Anthropology Society; Soyuz Postsocialist Studies Network; Association of Senior Anthropologists; Association for Africanist Anthropology; Society for Economic Anthropology; Society for Medical Anthropology; Association of Latina and Latino Anthropologists; Middle East Section; Association for Feminist Anthropology; Archeology Division; Culture and Agriculture; Society for Urban/National and Transnational/Global Anthropology; National Association of Student Anthropologists; Council for Museum Anthropology; Association for the Anthropology of Policy; National Association for the Practice of Anthropology; and Society for Latin American and Caribbean Anthropology